Deposition and Analysis of Al‐Rich c‐AlxTi1−xN Coating with Preferred Orientation. Issue 1 (6th October 2016) - Paseuth, Anongsack; Yamagata, Kazuo; Miura, Akira; Higuchi, Mikio; Tadanaga, Kiyoharu
Abstract : Metastable c‐Al x T1− x N is an important and well‐established hard coating in the tool industry. To improve the mechanical and thermal properties, Al‐rich c‐Al x Ti1− x N coatings with controllable preferred crystal orientations were fabricated via low‐pressure chemical vapor deposition (LP‐CVD) in an industrial plant, using an AlCl3 –TiCl4 –NH3 –Ar–H2 precursor system. The c‐Al x Ti1− x N coatings with (100)‐ and (111)‐preferred orientations and average x values of 0.82 and 0.73, respectively, comprised c‐Al(Ti)N/c‐Ti(Al)N nanolamellae with average compositions of c‐Al0.9 Ti0.1 N/c‐Al0.6 Ti0.4 N and c‐Al0.80 Ti0.20 N/c‐Al0.50 Ti0.50 N; the average lamellar periods were 7.7 and 4.5 nm, respectively. High‐resolution transmission electron microscopy indicated that the c‐Al(Ti)N/c‐Ti(Al)N nanolamellae were modulated along the <100> direction, implying coherent spinodal decomposition of c‐Al x Ti1− x N in the as‐deposited state. The hardness of the c‐Al x Ti1− x N coatings varied from 33 to 36 GPa, depending on the (100)‐ or (111)‐preferred orientation. Residual stress measurements in the as‐deposited state showed tensile stress values of 1.8 and 4.6 GPa for the (100)‐ and (111)‐oriented c‐Al x T1− x N coatings, respectively. This stress may be generated by the difference in the thermal expansion coefficient of the c‐Al x T1− x N coating and the carbide substrate and by coherency stress in the c‐Al(Ti)N/c‐Ti(Al)N nanolamellae. In situ high‐temperature X‐Ray diffraction results revealed high thermal stability up to 1000°C.